2019
DOI: 10.3390/w11040737
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mixing Processes in a Shallow Subtropical Reservoir and Their Effects on Dissolved Organic Matter

Abstract: A good understanding of the physical processes of lakes or reservoirs, especially of those providing drinking water to residents, plays a vital role in water management. In this study, the water circulation and mixing processes occurring in the shallow, subtropical Tingalpa Reservoir in Australia have been investigated. Bathymetrical, meteorological, chemical and physical data collected from field measurements, laboratory analysis of water sampling and an in-situ Vertical Profile System (VPS) were analysed. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In line with previous studies, noting DOM interference on fluorescence intensity only at very high concentrations (de Oliveira et al, 2018), the magnitude of DOM interference on the total algae sensor became significant only for very high organic matter levels, which were only very rarely measured at the reservoirs of this study (Wang et al, 2019). Nevertheless, with DOM amount and character strongly correlated with storm events (Awad et al, 2017;Wang et al, 2019), it was important to understand and quantify such interference, since the frequency and magnitude of extreme wet weather events might increase in the future (Pachauri et al, 2014). The availability of both measurements in-situ and concurrently, can provide the opportunity to adjust PC and chl-a readings in In our experiments, the sensor was able to accurately measure species with very small diameter cells, such as Aphanocapsa sp.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies, noting DOM interference on fluorescence intensity only at very high concentrations (de Oliveira et al, 2018), the magnitude of DOM interference on the total algae sensor became significant only for very high organic matter levels, which were only very rarely measured at the reservoirs of this study (Wang et al, 2019). Nevertheless, with DOM amount and character strongly correlated with storm events (Awad et al, 2017;Wang et al, 2019), it was important to understand and quantify such interference, since the frequency and magnitude of extreme wet weather events might increase in the future (Pachauri et al, 2014). The availability of both measurements in-situ and concurrently, can provide the opportunity to adjust PC and chl-a readings in In our experiments, the sensor was able to accurately measure species with very small diameter cells, such as Aphanocapsa sp.…”
Section: Discussionsupporting
confidence: 92%
“…In Tingalpa reservoir, that is a small subtropical Australian reservoir, previous studies found that heavy rainfall, especially occurring after a dry period, led to dramatic accelerated water mixing and significantly influenced water quality [23]. The water temperature and turbidity variation in the vertical direction were also studied in this reservoir as part of the same study.…”
Section: Introductionmentioning
confidence: 96%
“…UV 254nm , in combination with DOC and other basic water chemistry parameters has already been used to successfully predict disinfection byproduct formation potential from raw water quality (by modelling using artificial neural networks) [18][19][20]. Some studies, e.g., [21,22], have shown that the fDOM had a good correlation with the DOC because fDOM captures a sufficient amount of the DOC pool, although DOC compounds do exist that cannot be measured with the fDOM sensor [21]. This is one of the reasons why we used a fluorescence spectrometer with a resolution much higher than one wavelength, and combined the EEMs with the parallel factor analysis (PARAFAC).…”
Section: Introductionmentioning
confidence: 99%